Adoption Of Green Marketing Driven By Sustainable Environmental Initiatives In The Food And Beverage Sector - Ratih Puspitasari; Retno Martanti Endah Lestari; Mumuh Mulyana; Mashadi Mashadi (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study explores the adoption of green marketing strategies in the food and beverage industry within Bogor City, Indonesia. Employing a descriptive qualitative method, data were collected through questionnaires distributed to 146 industry managers across six sub-districts. The study evaluates the implementation of the green marketing mix—green product, green price, green place, and green promotion—using a holistic multiple case study design. Findings reveal a strong commitment to environmental sustainability, demonstrated by the use of eco-friendly raw materials, recyclable packaging, and environmentally focused promotional strategies. This research contributes to the existing literature by focusing on a specific industrial sector in a developing country context. It also emphasizes the growing role of consumer awareness in driving sustainable business practices. Keywords: Green Marketing, Sustainable Environmental Efforts, Environmental Impact, food and beverage industry